Future Trends in Disability and Its Determinants Among Chinese Community Patients With Anxiety Disorders: Evidence From a 5-Year Follow-Up Study - Liu, Zhaorui; Li, Peijun; Yin, Huifang; Li, Minghui; Yan, Jie; Ma, Chao; Ding, Hua; Li, Qiang; Huang, Zhengjing; Yan, Yongping; Kou, Changgui; Hu, Mi; et al. (Frontiers in Psychiatry, 2021)
Background: Anxiety disorders (ADs) are a group of disorders with a high disability rate and bring a huge social burden. In China, information on future trends in the disability among community ADs patients and its determinants are rare. The objectives of this study are to describe the future trends in the disability among ADs patients living in community and to investigate the determinants of the disability. Methods: Participants diagnosed with 12-month ADs in the China Mental Health Survey (CMHS) were followed up by telephone from April to June 2018 to assess the future trends in the disability in a five-year interval using the World Health Organization's Disability Assessment Schedule 2.0. The disability rate was reported and its determinants were analyzed by complex sample design multivariate logistic regression. Results: Totally 271 patients were interviewed by telephone and 33 informants finished proxy interviews. The disability rates were 45.9% and 14.3% among ADs patients at baseline and during the follow-up. Patients with general anxiety disorder (GAD) or agoraphobia with/without panic disorder (AGP) had the lower decrease and higher disability during the follow-up than patients with other subtypes. Patients aged in middle age (aged 40 to 49 years old, OR=11.12, 95% CI: 4.16-29.72), having disability at baseline (OR=7.18, 95% CI: 1.37-37.73), having comorbidity with three or more physical diseases (OR=9.27, 95% CI: 2.48-34.71), and having comorbidity with other mental disorders (OR=3.97, 95% CI: 1.13-13.96) had higher disability during the follow-up. Conclusions: The disability rate tends to decrease among ADs patients living in communities. Treatment priority should be given for ADs patients with disability and those in middle age. Treatments for the comorbidity of other mental disorders or physical diseases should be considered when treating anxiety.